Republic of San Marino : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of San Marino. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights the slow recovery of San Marino's economy after a deep recession following a series of financial sector shocks. Growth resumed in 2015 and accelerated in 2016 to an estimated 1 percent, thanks to stronger domestic and external demand. Moderate growth is expected in the near and medium term. GDP growth is projected to reach 1.3 percent in the medium term, driven by continued expansion in nonfinancial industries and services. However, following the current trend, the pace of growth would not be strong enough to bring output to precrisis levels over the next five years as risks remain tilted to the downside.